Detection of Anticompetitive Horizontal Mergers - Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
The paper develops a four-step framework to detect anticompetitive horizontal mergers. In the first step, an estimate of the impact of the merger on the market price needs to be derived. Subsequent, the second step of the framework has to assess whether such a predicted price increase would be sustainable post-merger. The third step needs to assess whether the identified efficiencies are substantial enough to at least hold the premerger price level. Finally, the fourth step has to consider the effects of a horizontal merger on other competition variables such as product variety, marketing as well as R&D post-merger.
Keywords: L41; K21; L40; 330; Competition policy; antitrust enforcement; mergers; unilateral effects; Horizontale Konzentration; Fusionskontrolle; Preiswettbewerb; Wettbewerbsbeschränkung; Wettbewerbsaufsicht; Theorie